PRIORITY TRENDS IN ENSURING THE ENERGY SECURITY OF UKRAINE IN THE TERMS OF EUROINTEGRATION - Oksana Mykoliuk (Сучасний стан наукових досліджень та технологій в промисловості, 2018)
The subject matter of the study is to find the priority tasks and to select ways to ensure the energy security of Ukraine as well as to identify its energy potential for accelerating the economic growth. The goal of the article is to study the trends and strategic prospects for creating, developing and ensuring the energy security of Ukraine under the conditions of European integration reforms. The following methods and ways of scientific research were used in the article: the dialectical and the system approach was used to generalize the scientific study; the method of logical generalization was used to study the existing situation and to justify the directions for ensuring the energy security, to substantiate the relevance of the topic, the goal and objectives of the study, to identify the essential features and threats of the excessive use of imported energy supplies; the method of grouping to systematize tasks and ways to diversify the energy consumption in Ukraine. Ukraine has a significant potential for accelerating the economic development and enhancing the energy security. The energy security is an important component of the national security of the state and one of the global problems of every country in the world. To realize the existing potential, Ukrainian laws and regulations should be reformed and the requirements of international agreements should be met, the relations with the countries of the European Union should be developed. The following tasks were solved: the current state of fuel and natural resources security of Ukraine was analyzed and the ways for improving the energy security were systematized, the trends in the development and the priorities of the strategic prospects of Ukraine in the context of integration processes were studied. The following results were obtained: the main steps to ensure the energy security of Ukraine, to enhance the cooperation with the EU countries, to strengthen the relations in the context of the energy security were highlighted, the available energy potential for accelerating the economic growth was substantiated. Conclusions. The need to neutralize threats to energy efficiency as a diversification of energy consumption in Ukraine is proved. This approach will ensure the international competitiveness of the Ukrainian economy, the prerequisites for membership in international organizations; it will also stimulate the renewal of the domestic energy industry. The prospects for further research in this area are the study of the development of the competitive energy market and transition to the energy-efficient use of energy resources in order to ensure the energy security of Ukraine.